1998
DOI: 10.1002/hep.510270236
|View full text |Cite
|
Sign up to set email alerts
|

EfficientIn Vitro vectorial transport of a fluorescent conjugated bile acid analogue by polarized hepatic hybrid WIF-B and WIF-B9 cells

Abstract: Efficient transport of bile acids, a typical characteristic of hepatocytes, is partially lost in most hepatoma cell lines and in normal hepatocytes after some days in culture. We have tested whether the polarized rat hepatoma-human fibroblast hybrid WIF (hybrids between W138 and Fao cells) cells previously obtained by our group were able to perform vectorial transport of the fluorescent bile acid derivative cholylglycylamidofluorescein (CGamF) towards the bile canaliculi (BC). Four different WIF clones were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 33 publications
(62 reference statements)
3
42
0
Order By: Relevance
“…5 ). Similar fl uorescent conjugates of bile acids have been extensively used to study the mechanisms of uptake and excretion of bile acids by hepatocytes (37)(38)(39)(40). These bile acid fl uorescent analogs were characterized in a previous study, where DCA-NBD and UDCA-NBD were shown to have a superfi cial location in lipid membranes and to interact preferentially with less ordered liposomes, in agreement with results obtained with unmodifi ed bile acids ( 14 ).…”
Section: Subcellular Distribution Of Bile Acid Derivativessupporting
confidence: 64%
“…5 ). Similar fl uorescent conjugates of bile acids have been extensively used to study the mechanisms of uptake and excretion of bile acids by hepatocytes (37)(38)(39)(40). These bile acid fl uorescent analogs were characterized in a previous study, where DCA-NBD and UDCA-NBD were shown to have a superfi cial location in lipid membranes and to interact preferentially with less ordered liposomes, in agreement with results obtained with unmodifi ed bile acids ( 14 ).…”
Section: Subcellular Distribution Of Bile Acid Derivativessupporting
confidence: 64%
“…Therefore, an in vitro model that closely resembles normal hepatocytes would be beneficial for elucidating the injury-inducing mechanisms of ethanol. It has been previously established that the WIF-B cell line, a rat hepatoma/human fibroblast hybrid, has many functional and morphological similarities to hepatocytes [7][8][9][10][11][12][13]. This cell line forms functional bile canaliculi, obtains a hepatocyte-like cell polarity, expresses many hepatocytespecific genes, and is stable over many passages.…”
Section: Discussionmentioning
confidence: 99%
“…This cell line forms functional bile canaliculi, obtains a hepatocyte-like cell polarity, expresses many hepatocytespecific genes, and is stable over many passages. This cell line has been extensively used to study the effects of hepatocyte-specific polarity on intercellular communication, bile acid transport, and protein and membrane trafficking pathways [8,[10][11][12]40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the proliferative potential of mature hepatocytes originating from small hepatocytes seems to be limited in vitro, indicating the requirement of alternative strategies for the generation of high numbers and possible in vitro mass production of bile-salt-and organic-anion-transportcompetent hepatocytes. Such alternative procedures might include: (1) culturing primary hepatocytes under proliferating conditions (Block et al, 1996;Michalopoulos et al, 1999); (2) further development of partially polarized hepatoma derived cell lines such as Wif-B (Bender et al, 1999;Bravo et al, 1998) or H4IIEC3 (Ng et al, 2000) cells; and (3) isolation, expansion and differentiation of bone-marrow-derived stem cells (Avital et al, 2001;Schwartz et al, 2002). The last of these procedures is especially attractive because a subpopulation of bonemarrow-derived stem cells can acquire differentiated hepatocellular metabolic functions (Avital et al, 2001;Schwartz et al, 2002), has the capability to repopulate regenerating liver in vivo (Avital et al, 2001) and can restore certain biochemical functions of diseased liver (Lagasse et al, 2000).…”
Section: Discussionmentioning
confidence: 99%